Lingual Markers in Da'wah Messages in a Movie Entitled Ustad Millennial - Laili Etika Rahmawati; Ristika Dwi Pramutya (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
The purpose of this study is to describe the form of lingual markers and da'wah messages that exist in the dialogue of the film "Ustad Millenial". The study used a qualitative descriptive method. The data source of this research is the dialogue of the film "Ustad Millenial". The research data are oral data containing lingual markers which include da'wah messages in the dialogue of the film "Ustad Millenial". The data collection technique used in this study is the note-taking technique. Data was collected and recorded then recorded and then identified. The next step is the data is grouped based on their respective categories according to the existing theory. The results of this study indicate the lingual markers of da'wah messages that exist in the dialogue of the film "Ustad Millenial". Lingual markers are one of the branches of pragmatic studies. Where in this study learn about the structure of language related to how a language is used in communication. The conclusions of the lingual markers of da'wah messages in the film "Ustad Millenial" are divided into 6 categories, namely assertive, directive, commissive, declarative, rogative, expressive speech acts.